2016
DOI: 10.1186/s12284-016-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in breeding for high grain Zinc in Rice

Abstract: Zinc (Zn) is one of the most essential micronutrients required for the growth and development of human beings. More than one billion people, particularly children and pregnant women suffer from Zn deficiency related health problems in Asia. Rice is the major staple food for Asians, but the presently grown popular high yielding rice varieties are poor supplier of Zn in their polished form. Breeding rice varieties with high grain Zn has been suggested to be a sustainable, targeted, food-based and cost effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 153 publications
(164 reference statements)
8
147
0
1
Order By: Relevance
“…Another study from China found results similar to ours [78]. Rice is the main staple of Asians, but in current high-yielding rice varieties the supply of zinc is poor, as polishing and shelling cause a huge loss of zinc [81,82]. Other reason is possible that discrepancies in levels of trace elements between different countries are partly due to environmental factors, but specific reasons need to be explored further.…”
Section: Discussionsupporting
confidence: 68%
“…Another study from China found results similar to ours [78]. Rice is the main staple of Asians, but in current high-yielding rice varieties the supply of zinc is poor, as polishing and shelling cause a huge loss of zinc [81,82]. Other reason is possible that discrepancies in levels of trace elements between different countries are partly due to environmental factors, but specific reasons need to be explored further.…”
Section: Discussionsupporting
confidence: 68%
“…Recent progress in developing molecular markers will help facilitate mainstreaming (Babu et al, 2013, Swamy et al, 2016). As new varieties are developed and released, they should include the biofortified trait as a matter of standard practice.…”
Section: A Future Vision: Institutional Leadership To Drive and Guidementioning
confidence: 99%
“…In general, concentration of Zn such as 500 mgKg -1 may be toxic to crops resulting reduced crop yield [12]. Recent report reveals that in India and Indonesia high zinc rice lines are in advanced stages of evaluation [13,14]. These high zinc line have 18-22 mgKg -1 with acceptable yield potential, grain quality and agronomic traits.…”
Section: Introductionmentioning
confidence: 99%